2001
DOI: 10.1073/pnas.161191698
|View full text |Cite
|
Sign up to set email alerts
|

Supersensitivity to anandamide and enhanced endogenous cannabinoid signaling in mice lacking fatty acid amide hydrolase

Abstract: The medicinal properties of marijuana have been recognized for centuries, but clinical and societal acceptance of this drug of abuse as a potential therapeutic agent remains fiercely debated. An attractive alternative to marijuana-based therapeutics would be to target the molecular pathways that mediate the effects of this drug. To date, these neural signaling pathways have been shown to comprise a cannabinoid receptor (CB1) that binds the active constituent of marijuana, tetrahydrocannabinol (THC), and a post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

68
1,065
0
11

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,197 publications
(1,144 citation statements)
references
References 38 publications
68
1,065
0
11
Order By: Relevance
“…Key to the implementation of discovery metabolite profiling (DMP) was the supposition that the absolute mass ion intensities measured during LC-MS analysis could be used in a broad mass-scanning mode to quantify the relative levels of metabolites in tissue samples and thereby obviate the need for internal standards ( Figure 1B). To test this premise, we compared the LC-MS metabolite profiles of central nervous system (CNS) tissues from wild-type mice and mice lacking the enzyme FAAH (9) [FAAH(-/-) mice], which degrades several neural signaling lipids in ViVo (10), (10,12) and thus provided an excellent model for testing the capacity of DMP to identify both known changes in the levels of specific FAAH substrates and potentially novel metabolites regulated by this enzyme in ViVo.…”
Section: Development Of An Untargeted Standard-free Approach For Commentioning
confidence: 99%
“…Key to the implementation of discovery metabolite profiling (DMP) was the supposition that the absolute mass ion intensities measured during LC-MS analysis could be used in a broad mass-scanning mode to quantify the relative levels of metabolites in tissue samples and thereby obviate the need for internal standards ( Figure 1B). To test this premise, we compared the LC-MS metabolite profiles of central nervous system (CNS) tissues from wild-type mice and mice lacking the enzyme FAAH (9) [FAAH(-/-) mice], which degrades several neural signaling lipids in ViVo (10), (10,12) and thus provided an excellent model for testing the capacity of DMP to identify both known changes in the levels of specific FAAH substrates and potentially novel metabolites regulated by this enzyme in ViVo.…”
Section: Development Of An Untargeted Standard-free Approach For Commentioning
confidence: 99%
“…Both endocannabinoids affect male reproductive functions: 2-arachidonoylglycerol has a pivotal role in spermatogenesis, by promoting the meiotic progression of germ cells [16]; AEA controls sperm functionality by reducing motility, capacitation, and acrosome reaction [17,18], and it also reduces the spermatogenic output by inducing apoptosis of Sertoli cells [15]. AEA signaling depends on its endogenous content, that in vivo is strongly controlled by FAAH [19]. Remarkably, recent studies have shown that among the different components of the ''endocannabinoid system'' (i.e., AEA-binding receptors and metabolic enzymes) in Sertoli cells, only FAAH is a target of follicle-stimulating hormone (FSH) [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…FAAH (À/À) mice have been shown to possess quantities of anandamide and other FAAs (eg, oleamide, PEA, OEA) in the brain and other areas more than 10 times the levels seen in wild-type mice. Accordingly, FAAH (À/À) mice represent a useful tool to evaluate the physiological function of these lipid signaling molecules (Cravatt et al, 2001;Clement et al, 2003). In addition to displaying dramatically enhanced responses to intraperitoneal injections of anandamide, FAAH (À/À) mice display CB 1 receptor mediated hypoalgesic responses to radiant heat and inflammatory stimuli (Cravatt et al, 2001;Lichtman et al, 2004b).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, FAAH (À/À) mice represent a useful tool to evaluate the physiological function of these lipid signaling molecules (Cravatt et al, 2001;Clement et al, 2003). In addition to displaying dramatically enhanced responses to intraperitoneal injections of anandamide, FAAH (À/À) mice display CB 1 receptor mediated hypoalgesic responses to radiant heat and inflammatory stimuli (Cravatt et al, 2001;Lichtman et al, 2004b). In parallel with the transgenic models, several pharmacological inhibitors of FAAH have been developed and shown to elicit cannabinoid-receptor mediated analgesia, notably reversible a-ketoheterocyle inhibitors (eg, OL-135), and irreversible carbamate inhibitors (eg, URB-597).…”
Section: Introductionmentioning
confidence: 99%